Effectiveness of Structured Educational Program on Nurses’ Practices Concerning Therapeutic Communication at Cardiac Care Units in Holy Karbala Governorate Hospitals - dawood, hussam; hassan, Hakemia (Iraqi National Journal of Nursing Specialties, 2018)
Abstract Objectives: This study aimed to evaluate the effectiveness of an educational program on nurses' practices concerning therapeutic communication.Methodology: A quasi experimental design was carried out at Karbala Center for Cardiac Diseases and Surgery, Imam Hussein Medical City and Al-Handia General Hospital for period 10th June 2017 to the 15th of August 2018. The program and instruments were constructed and developed by the researcher to measure the purpose of the study. Purposive sample comprised of (57) nurses were divided into two groups, study and control groups. The questionnaire consisted from two parts, first part is related to nurses' demographic characteristics and second part which include practices checklist (17) items concerning therapeutic communication. The analysis of data was performed through the application of descriptive statistics and inferential statistics.Results: The results of the study showed that the effectiveness of educational program regarding nurses' practices for therapeutic communication is a positive. It also shows that there are highly significant differences in the study group between pre-and posttests overall (17) items related to nurse's practicesRecommendations: The study recommended that establishing new standard program for therapeutic communication suitable for cardiac care nurses in Iraq depending on standard program of foreign and Arabic countries and upon the results of this study. Also, the Ministry of Health should be approved competency of registered nurse in therapeutic communication which apply in overall world.